2017
DOI: 10.18632/oncotarget.18506
|View full text |Cite
|
Sign up to set email alerts
|

p53, p63 and p73 in the wonderland ofS. cerevisiae

Abstract: Since its discovery in 1979, p53 has been on the forefront of cancer research. It is considered a master gene of cancer suppression and is found mutated in around 50% of all human tumors. In addition, the progressive identification of p53-related transcription factors p63 and p73 as well as their multiple isoforms have added further layers of complexity to an already dense network. Among the numerous models used to unravel the p53 family mysteries, S. cerevisiae has been particularly useful. This seemingly nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Also, overexpression of wild-type p53 could generate prion seeds de novo that, instead of providing p53 activity, cause aggregation of the p53 mutant protein causing increased loss of activity. p53 prion protein could also trap and inactivate its related transcription factors, p63 and p73 ( Billant et al., 2017 ), which could increase cancer pathology. In contrast, prion-like aggregates that do not multiply would have a more limited capacity to inactivate WT p53, p63, or p73.…”
Section: Discussionmentioning
confidence: 99%
“…Also, overexpression of wild-type p53 could generate prion seeds de novo that, instead of providing p53 activity, cause aggregation of the p53 mutant protein causing increased loss of activity. p53 prion protein could also trap and inactivate its related transcription factors, p63 and p73 ( Billant et al., 2017 ), which could increase cancer pathology. In contrast, prion-like aggregates that do not multiply would have a more limited capacity to inactivate WT p53, p63, or p73.…”
Section: Discussionmentioning
confidence: 99%
“…Although fungi lack p53, yeast has long been an attractive system for characterizing p53 function using transcriptional reporters whose activity depends on p53 oligomerization, nuclear localization, and DNA binding (Sharma et al 2016;Billant et al 2017). Analysis using a yeast system of 76 mutants representing 54% of over 15,000 total reported missense mutations in the p53 core domain ("IARC p53 Database (p53.iarc.fr)") found that most were dominant-negative, loss-of-function alleles (Dearth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Informative phenomic models have been developed for multiple human diseases, including cystic fibrosis, neurodegenerative disorders, and cancer [9,282,283,284]. Molecular models include mutations in conserved residues of yeast homologs of a disease gene and introduction of human alleles into yeast.…”
Section: Discussionmentioning
confidence: 99%